2019
DOI: 10.1097/mpg.0000000000002380
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Effects of Cholestatic Liver Disease in Childhood on Neuropsychological Outcomes and Neurochemistry

Abstract: OBJECTIVES. Children with liver disease have increased risk of long-term cognitive deficits. We differentiated between the effects of chronic liver disease from that associated with transplantation by recruiting children with cholestatic liver disease with and without transplantation. METHODS. Psychometric measures and magnetic resonance spectroscopy were obtained for 3 groups of children: stable liver disease (SLD) without transplantation; cholestatic liver disease (CLD) from birth with transplantation; and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 30 publications
0
34
1
Order By: Relevance
“…LT does not correct the impairment (79,80). In addition, overall health related quality of life is inferior, and prevalence of mental health problems, in particular in adolescents and young adults is higher compared to the general population (81,82).…”
mentioning
confidence: 98%
“…LT does not correct the impairment (79,80). In addition, overall health related quality of life is inferior, and prevalence of mental health problems, in particular in adolescents and young adults is higher compared to the general population (81,82).…”
mentioning
confidence: 98%
“…[35] Previous research showed a correlation between cholestasis and impaired cognitive outcomes. [36,37] Cholestasis might cause brain lesions, especially in the white matter, which is believed to be the neural foundation for general intelligence. [38] Recently, Talcott et al showed alterations in the brain biochemistry of children with liver disease, including children with asymptomatic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…[38] Recently, Talcott et al showed alterations in the brain biochemistry of children with liver disease, including children with asymptomatic liver disease. [37] All children with BA are faced with cholestasis prior to KPE surgery, and many also after KPE, making this a possible cause for neurodevelopmental impairments. Major surgery in young children itself may also be a possible risk factor for impaired neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that children express anxiety regarding medications citing changes to physical appearance and conflict with parents as reasons for non‐adherence 20‐23 . In the current cohort, we found that some of our patients developed depression and/or anxiety related to liver disease and transplantation, which affected their psychological development.…”
Section: Discussionmentioning
confidence: 54%
“…This is comparable to the general population as only It has been noted that children express anxiety regarding medications citing changes to physical appearance and conflict with parents as reasons for non-adherence. [20][21][22][23] In the current cohort, we found that some of our patients developed depression and/or anxiety related to liver disease and transplantation, which affected their psychological development. Although formal quality-of-life questionnaires were not performed, enquiries of survivors identified symptoms consistent with depression and anorexia nervosa either currently or in the past (with some patients having a formal diagnosis consistent with DSM IV criteria for mental health conditions).…”
Section: Discussionmentioning
confidence: 63%